Comunicação sem objeto: dança contemporânea - Almeida Neto, Arthur Marques de (2016)
This research investigates the media bios (SODRE, 2006) that turned into a communicational and economical device of biopolitics call (PRADO, 2013) the term 'contemporary dance'. In Brazil, in recent years, many artistic works began to name themselves as 'contemporary dance', practicing such generality that makes it impossible to identify the object to which the term refers. The proposal is to investigate the phenomenon of emptying this expression, gathering as corpus advertisements circulating on the Internet in the form of flyers of courses, classes or workshops, the texts and the results of the notices of Petrobrás Cultural Program and dance programs for television art channels SESC TV, Arte1 channel and Brazil Channel. This is on the assumption that these economic and communicational devices, when sanctioned institutional and legally act as biopolitical power devices, legislating on what should live or die. The goal is to bring visibility to the type of call performed by the devices calling on the expression 'contemporary dance' as synonymous with the term 'dance', interpellating individuals as 'contemporary dance' subjects-artists. Seeks to demonstrate that, in constant exchange with the environment, biopolitical devices of economic and communicational power are naturalizing 'contemporary dance' expression as non-specific. The theoretical framework prioritizes the biopolitics relations between media and body, reading them with Corpomídia Theory (KATZ and GREINER, 2005), and authors such as Foucault (2008, 1999), Althusser (1996) and Franko (2002)